Characteristics of Phosphate Sorption on Surface Sediments: A Study in Kendari Bay - Aisyah, Siti; Rohaeti, Eti; Budi Santoso, Arianto; Rafi, Mohamad (BRIN Publishing, 2024)
Phosphate adsorption and desorption are significant processes that influence the presence of phosphate in aquatic ecosystems and regulate the concentration of phosphate at the water-sediment interface. This research aims to investigate the characteristics of phosphate adsorption and desorption in Kendari Bay sediments, study the relationship between adsorption capacity and sediment characteristics and its phosphorus fraction, and evaluate its potential contribution to the overlying water column. Physicochemical measurements of the water and sediments were performed in the sampling location and the laboratory. Two types of adsorption-desorption kinetics models and two types of isothermal adsorption models were used to estimate the adsorption rate and capacity of the surface sediments. Adsorption kinetics and desorption kinetics experiments produced pseudo-second-order kinetic model equations with regression coefficients (R2) of 0.865–0.936 and 0.886–0.947, respectively. The isothermal adsorption experiment follows the Langmuir equation model with R2 = 0.964. The maximum adsorption capacity (Qmax) value was 156.3–227.3 mg/kg, and the phosphate concentration value at zero equilibrium (EPC0) was 0.0026–0.0047 mgP/L. Notably, the EPC0 value was higher than the SRP concentration, indicating that the resuspension of phosphate ions from sediment into the water column could occur. Furthermore, there was a correlation between Qmax values with OP, Al-P, Fe-P, clay particles, and organic materials. Potential practical applications may include integrating sediment adsorption capacity data into ecosystem models to inform nutrient management strategies and promote sustainable coastal development in Kendari Bay and beyond.